An Overview of Inter-Connectivity and Security in a Smart Hospital Building (International Journal of Innovative Research in Engineering & Management, 2023)
Significant advancements in the past few  years have resulted in improved Smart Building  technologies for connectivity and protection. This article  provides an overview of these developments. In addition,  we provided a patient nurture scheme for clinic buildings  as well as a layered Building Management System (BMS)  architecture in this article. Then we conducted a  comparison of our system to other comparable systems and  highlighted the advantages of our method. Furthermore,  we suggested several security measures based on the  design and further study. In addition, this article includes a  comparison of our system to other comparable systems.  The advantages of our enterprise are then enumerated and  discussed. Finally, we researched and utilized the Contiki  OS and the Cooja emulator, as well as creating  simulations, to get a more comprehensive and truthful picture of our system. The consequences of the data packet  transfer are important since the protocol we employ has a  very low proportion of packets lost, if not none at all With  the Cooja simulator, we watch data in and into of the  networks in real time. As a result, it seems to be a very  helpful tool that provides, in addition to traffic, diagrams  and other data that characterize our system. We want to  mimic our whole system in the future using technologies  like the Cooja emulator. We will then proceed with the  installation of such a system if the outcomes are as  anticipated. This article will serve as a starting point for  making better choices in the future when developing smart  structure systems.
Keywords: BMS; Coap; Interoperability; NDN; Smart Buildings